Dynamic disorganization of synaptic NMDA receptors triggered by autoantibodies from psychotic patients - Jézéquel, Julie; Johansson, Emily M.; Dupuis, Julien P.; Rogemond, Véronique; Gréa, Hélène; Kellermayer, Blanka; Hamdani, Nora; Le Guen, Emmanuel; Rabu, Corentin; Lepleux, Marilyn; Spatola, Marianna; Mathias, Elodie; et al. (Nature communications, 2017)
The identification of circulating autoantibodies against neuronal receptors in neuropsychiatric disorders has fostered new conceptual and clinical frameworks. However, detection reliability, putative presence in different diseases and in health have raised questions about potential pathogenic mechanism mediated by autoantibodies. Using a combination of single molecule-based imaging approaches, we here ascertain the presence of circulating autoantibodies against glutamate NMDA receptor (NMDAR-Ab) in about 20% of psychotic patients diagnosed with schizophrenia and very few healthy subjects. NMDAR-Ab from patients and healthy subjects do not compete for binding on native receptor. Strikingly, NMDAR-Ab from patients, but not from healthy subjects, specifically alter the surface dynamics and nanoscale organization of synaptic NMDAR and its anchoring partner the EphrinB2 receptor in heterologous cells, cultured neurons and in mouse brain. Functionally, only patients’ NMDAR-Ab prevent long-term potentiation at glutamatergic synapses, while leaving NMDAR-mediated calcium influx intact. We unveil that NMDAR-Ab from psychotic patients alter NMDAR synaptic transmission, supporting a pathogenically relevant role. Autoantibodies are found in neuropsychiatric conditions but without clear cellular mechanism and disease relevance. This study shows higher prevalence of autoantibodies against NMDAR receptors in schizophrenia patients, and patient-associated antibody can alter synaptic receptor trafficking and plasticity.